(3efgLjI Yed dGSJOGeI GdGScGf GdGbJUGOi (B:s c - (3,GdGA QeVGf YHO GdMcje eNJGQs; (3eMeO MSjf YHO GdbGOQs; (3gjfGQ CHh GdeLO GMeOs (2023)
(3JYO GSJOGeI GdeHGfiGJLGg Ph GgejI HGdZI NGUI ai bWGY GdGScGf GdPi gh eMhQ GQJcGR ai GdGbJUGO MjK jSJgdc bWGY GdJTjO GcKQ ef (B40% (3ef GLeGdi GdWGbI YGdejG (B,(3ceG jeKd GSJgdGc bWGY GdGScGf ai eUQ eG jYGOd (B42.3% (3ef GLeGdi GSJgdGc GdWGbI ai eUQ WHbG deQcR GdJYHFg hGdGMUGA YGe (B2020.(3dPdc JhLg GdHMK dOQGSI eYOdGJ GSJgdGc GdWGbI ai GdGScGf GdGbJUGOi ai eQMdI GdJTZjd (B.(3hef Ke OQGSI JMbjb GbUi eYOd JQTjO GdWGbI (B,(3ehGO GdHfGA (B,(3hUhdG Gdi cjajI JMhjd gPg GdaFGJ ef GdeHGfj GdScfjg GdGbJUGOjI Gdi eHGfi eSJOGeI HGSJNOGe GdeYGdLGJ GdHjFjI hGdejcGfjcjg ddGSJaGOg ef GdWGbGJ GdeJLOOI GdfXjag hJhXjagG aiGdeHGfi GdScfjI dJhdjO GdWGbI GdcgQHGFjI hHGbd JGKjQ SdHi Ydi GdHjFg (B.s
The sustainability of buildings is a trend of great importance, especially in the housing sector, which is the focus of the economy, as the construction sector consumes more than 40% of the total energy globally, and the consumption of the housing sector in Egypt represents the equivalent of 42.3% of the total energy consumption in Egypt, according to the Mobilization Center. And statistics in 2020. Therefore, the research was directed to study energy consumption rates in economic housing in the operating phase. And then studying the achievement of the maximum rate of energy conservation by studying methods and systems of energy conservation, building materials, and how to convert these categories of economical residential buildings into sustainable buildings using environmental and mechanical treatments to take advantage of clean renewable energies and employ them in residential buildings to generate electric power at a lower rate. negative impact on the environment
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ (B132-136.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdGScGfs -- (3eUQs; (3GdGScGf GdGbJUGOis -- (3eUQs; (3GdJfejI GdeSJOGegs -- (3GdGScGf GdGbJUGOis -- (3GdGScGf GdeSJOGes